(3TQM GdQSGdI GdYVOjI aj GdhVYs - (3GdSeQbfOj, CHh GdbGSe Hf CHj HcQ, cGf MjG (B888(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj NU GdEfSGf HeYQaI ChVGY GdcdGe heHGfjg hLYd GdMQha CUhd cdeJg hXQha eYGfjg hGdUdGI Ydi GdeTJb ef eUOQ GdaVd hGdMce GdLGeY deMGSf GdCaYGds
(3BNQgG (B:s
(3HOaY eG YSi Cf jNWQ HHYV GdChgGe hgh Cf GdMce HGdLRFjI hGdcdjI hGdYdejI hGdehUhdjI hCeKGdgG ddCdaGX EfeG gh HGYJHGQ eG GSJYed ajgG GdeYGfjajMJed Cf jJhge dGSJYeGdg aj GdLRFjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 173s
(3eYLe GdeDdajf(B: 2 / 643s
(3cTa GdXfhf(B: 1 / 898s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GddZIs